2010
DOI: 10.1007/s00280-010-1266-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of hepatic arterial infusion of cisplatin in combination with intravenous liposomal doxorubicin in patients with advanced cancer and dominant liver involvement

Abstract: Purpose We conducted a phase I study of hepatic arterial infusion (HAI) cisplatin and systemic chemotherapy in patients with advanced cancer and dominant liver involvement. Methods Patients were treated with HAI cisplatin 100–125 mg/m2 (and 3,000 IU heparin) intraarterially and liposomal doxorubicin (doxil) 20–35 mg/m2 IV (day 1) every 28 days. A “3 + 3” study design was used. Results Thirty patients were treated (median age, 56 years). Diagnoses were breast cancer (n = 11), colorectal cancer (n = 8), ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In that study, 3 (27%) patients had a PR and 5 (45%) had SD for ≥4 months and antitumor activity was particularly noted in patients with breast cancer and melanoma. [5]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, 3 (27%) patients had a PR and 5 (45%) had SD for ≥4 months and antitumor activity was particularly noted in patients with breast cancer and melanoma. [5]…”
Section: Discussionmentioning
confidence: 99%
“…This combination was well tolerated and was associated with rates of partial response [1] and stable disease (SD) ≥4 months of 11% and 32%, respectively [4]. We have also reported that HAI of cisplatin combined with IV liposomal doxorubicin was associated with a PR rate of 7% and an SD ≥4 months a rate of 45% [5]. In another phase I study of HAI paclitaxel in patients with advanced cancer and dominant liver involvement, results were disappointing.…”
Section: Introductionmentioning
confidence: 99%
“…Also, docetaxel has been occasionally used in regional therapy, with some responses noted in squamous cell carcinoma of the lung [20], hypopharynx [21], head and neck, [22] and breast metastatic to the liver [8]. We previously reported that HAI oxaliplatin combination therapy has antitumor activity in patients with colorectal cancer and predominant liver metastases [23] and that HAI cisplatin and IV liposomal doxorubicin has antitumor activity in breast cancer with hepatic metastases [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In patients with breast cancer the median OS was 8.5 months, compared with 5.3 months for all other tumor types. 86 The use of this regimen seems to be safe and potentially has benefits in terms of RR, but more data are required before any judgment of a potential survival benefit can be made.…”
Section: Hepatic Artery Infusion Chemotherapy and Noncolorectal Livermentioning
confidence: 98%
“…86 A total of 30 patients were included (11 breast cancer, 8 CRLM, 4 ocular melanoma, and 7 other: HCC/gastric/pancreatic/head and neck/neuroendocrine/cutaneous melanoma/leiomyosarcoma). The trial was designed to evaluate safety and toxicity but also reported on outcomes.…”
Section: Hepatic Artery Infusion Chemotherapy and Noncolorectal Livermentioning
confidence: 99%